Caracterization of the SOS response in Leptospira interrogans sorovar Copenhageni - Fonseca, Luciane Schons da (2015)
Leptospira is a basal genus in an ancient group of bacteria, the spirochetes. The pathogenic species are responsible for leptospirosis, a disease with worldwide distribution and of public health importance in developed tropical countries. L. interrogans serovar Copenhageni is the agent for the majority of human leptospirosis in Brazil. In this work, we used a great variety of experimental approaches to characterize the SOS system in this serovar, to identify its impact in general DNA damage response, as well as to assess the DNA repair toolbox owned by pathogenic and saprophytic leptospires. We identified an additional repressor LexA, acquired by lateral gene transfer, exclusively in serovar Copenhageni. We also observed that UV-C irradiation led to massive death of cells and blockage of cell division in the survivors. Both repressors were active and we identified the sequences responsible for binding to promoters. However, the LexA1 SOS box was redefined after a de novo motif search on LexA1 ChIP-seq enriched sequences. This regulator was able to bind to at least 25 loci in the genome. DNA damage also caused a massive rearrangement of metabolism: increase in expression was observed in transposon and prophage genes, in addition to DNA repair pathways and mutagenesis inducers; on the other hand, motility, general metabolism and almost all virulence genes were repressed. Two induced prophages provided several proteins with useful functions. We also assessed the DNA repair-related genes presented by the three species of Leptospira: the saprophytic L. biflexa, the facultative pathogen L. interrogans and the obligatory pathogen L. borgpetersenii. There are more diversity and redundancy of repair genes in L. interrogans in comparison with the other species. Lateral gene transfer seems to be an important supplier of DNA repair functions. In addition, leptospires share characteristics of both Gram-positives and Gram-negatives bacteria. Representative genes from several different pathways were induced during infection of susceptible mice kidneys, suggesting DNA repair genes are active while causing disease. All these data suggest mobile genetic elements are the major forces in leptospiral evolution. Moreover, during DNA damage response, several SOS-dependent and independent mechanisms are employed to decrease cell growth and virulence in favor of controlled induction of mechanisms involved in genetic variability.